Perceptually guided authoring of image based representations - Morvan, Yann (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2007)
The creation of digital visual content has become a major activity in a broad range of industries. A huge quantity of labour is invested in related tasks, from modeling to de-noising of captured data. There has been significant research in computer graphics aimed at automating or even bypassing some of these tasks. In the field of rendering, one such direction is the image-based approach, which allows new views to be computed from available images and rudimentary geometric information. Perceptually informed graphics, albeit so far predominantly explored to achieve machine-hours savings, is another area of great potential.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin